Contradictory Constructions of the Crisis in Zimbabwe (Historia, 2021)
EnglishA striking aspect of the Zimbabwean crisis has been the struggle over its meaning within Zimbabwe, Africa and the wider world. The discussion has reopened questions about the legacy of the liberation struggle for contemporary politics and the issues of its “unfinished business”, especially in the continuing racial imbalance in land ownership in southern Africa. A second issue has been the question of democracy in Zimbabwe and the state’s legitimacy given highly contested results in a series of elections (in 2000, 2002 and 2005) and the closing of space for opposition forces between, as well as within elections. A third important area of debate is over the significance of global pressures in creating the crisis. At least two major approaches have emerged – one largely supportive of the actions of the Zimbabwean government and the other profoundly opposed to it. For one section of opinion, the key issue in understanding Zimbabwe’s troubles, is the refusal of forces within and without Zimbabwe to accept the radical reform which has resulted in the transformation of commercial farmland from white to African farmers. A central proposition of the opposing view is that the current crisis is less about finishing the tasks of the liberation struggle through the land reform, than a reaction by the current government in Zimbabwe to the most serious challenge to its power since independence. This study will attempt to assess the merits of the debate.    AfrikaansTeenstrydige Konstruksies van die Krisis in Zimbabwe ’n Treffende aspek van die Zimbabwese krisis is die teenstrydige menings wat oor die betekenis daarvan in Zimbabwe, Afrika en die wyer wêreld gehuldig word. Die bespreking daarvan laat opnuut vrae ontstaan oor die invloed van die vryheidstryd op eietydse politiek, asook die “onafgehandelde besigheid” daarvan, veral wat die voortgesette wanbalans van rasse se grondeienaarskap in suidelike Afrika betref. ’n Tweede aspek wat aandag verdien, is vrae oor die wettigheid van die demokrasie in Zimbabwe, veral gesien in die lig van die uiters betwisbare uitslae van ’n aantal verkiesings (in 2000, 2002 en 2005) en die afname aan ruimte wat die regering tussen die verkiesings, sowel as daartydens, aan die opposisie gelaat het. ’n Derde belangrike debatspunt handel oor die invloed wat globale druk op die ontstaan van die krisis gehad het. Ten minste twee hoofstroom benaderings het ontstaan – een daarvan grootliks ondersteunend van die aksies van die Zimbabwese regering en die ander besonder sterk daarteen gekant. Vir die een opiniegroep lê die sleutel tot begrip vir Zimbabwe se probleme opgesluit in die weiering van magte binne en buite Zimbabwe om die radikale hervorming wat die transformasie van eienaarskap van kommersiële plaasgrond van wit na swart boere tot gevolg gehad het, te aanvaar. ’n Sentrale veronderstelling van die opponerende opiniegroep is dat die huidige krisis minder oor die afhandeling van die take van die vryheidstryd deur grondhervorming gaan, en eerder die huidige regering in Zimbabwe se reaksie is op die ernstigste magsuitdaging waarteenoor dit sedert onafhanklikheidswording te staan gekom het. Hierdie studie poog om die meriete van die debat te bepaal.
Keywords: Zimbabwe; crisis; contradictory meanings; land reform; repression; democracy; nationalism; imperialism; krisis; teenstrydige betekenisse; grondhervorming; onderdrukking; demokrasie; nasionalisme; imperialisme